Durable Complete Response in a Melanoma Patient With Unknown Primary, Associated With Sequential and Severe Multi-Organ Toxicity After a Single Dose of CTLA-4 Plus PD-1 Blockade: A Case Report - Matull, Johanna; Livingstone, Elisabeth; Wetter, Axel; Zimmer, Lisa; Zaremba, Anne; Lahner, Harald; Schadendorf, Dirk; Ugurel, Selma (Frontiers in Oncology, 2020)
Monoclonal antibodies blocking PD-1 and CTLA-4 immunological checkpoints lead to durable tumor responses in a considerable number of advanced melanoma patients. Besides their anti-neoplastic efficacy, these immune checkpoint inhibitors cause a wide range of immune-related adverse events (irAEs), often enforcing an early discontinuation of therapy. The value of irAEs as a predictive marker for better patient survival is still debated. We report here on a melanoma patient with intramuscular, pulmonary, and bone metastases who developed severe sequential irAEs involving multiple organ systems after single application of a combined immunotherapy with ipilimumab plus nivolumab, followed by a durable complete response despite an early discontinuation of therapy.